Development and Psychometric Validation of a Reusable Personal Protective Equipment Cost-Efficiency and Durability Instrument Among Indonesian Healthcare Workers - Rizky Ratria Kusumawardhani; Darmawan Ismail (Community Medicine and Education Journal, 2026)
Personal protective equipment (PPE) is central to protecting healthcare workers from occupational infection, yet the COVID-19 pandemic exposed the high cost, supply fragility and waste burden of single-use PPE, generating interest in reusable systems whose value depends on economic efficiency and material durability. Validated instruments capturing the end-user perspective on these dimensions are scarce. This study developed and evaluated the psychometric properties of a ten-item, healthcare-worker–reported instrument measuring the cost efficiency and material durability of reusable PPE. An analytical cross-sectional, COSMIN-guided instrument-validation study was conducted at Dr. Moewardi Regional General Hospital, Surakarta, Central Java, Indonesia (March–July 2025) and reported per STROBE. Thirty healthcare workers recruited by consecutive sampling each rated conventional disposable Level-3 PPE and a reusable alternative, yielding 60 paired assessments on five-point Likert items. Construct (known-groups) validity used Spearman correlations with 95% confidence intervals; structural validity used exploratory factor analysis with Horn parallel analysis; convergent validity used Average Variance Extracted (AVE) and Composite Reliability (CR); internal consistency used Cronbach's alpha and McDonald's omega with a bootstrap CI. All items discriminated PPE type (Spearman rho -0.383 to -0.556, all p<0.05). Sampling adequacy was excellent (Kaiser-Meyer-Olkin=0.897; Bartlett p<0.001), and a single factor explained 57.1% of variance, corroborated by parallel analysis. Factor loadings ranged 0.642-0.820; AVE was 0.525 and CR 0.917. Internal consistency was excellent (alpha=0.916; omega=0.917; bootstrap 95% CI 0.869-0.943), with a standard error of measurement of 1.8 scale points and no floor effects. The instrument is valid, reliable and unidimensional, supporting value-based PPE procurement, infection-prevention monitoring and sustainable-healthcare policy in Indonesian hospitals.